2011
DOI: 10.1063/1.3665130
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric nonlinearity in magnetoelectric laminate sensors

Abstract: High-resolution current sensor utilizing nanocrystalline alloy and magnetoelectric laminate composite Rev. Sci. Instrum. 83, 115001 (2012) A nonlinearity in the magnetoelectric coefficient, a Nonlin ME , of Metglas=Pb(Zr,Ti)O 3 (PZT) and Metglas=Pb(Mg 1=3 ,Nb 2=3 )O 3 -PbTiO 3 (PMN-PT) laminate sensors has been observed. This nonlinearity was found to be dependent on the dc magnetic bias (H dc ) and frequency of the ac drive field (H ac ). The maximum value of a Nonlin ME for both types of composites was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…11 Recently, a modulation mode sensor which used a 2nd order ME nonlinearity was reported that transferred low-frequency target signals to higher frequencies. 12 In this method, an exciting carrier signal provided an effective means to reduce 1/f noise, to increase the signal-to-noise ratio (SNR), and to mitigate vibrational noise that is compared to a conventional passive mode scheme. 13 The effectiveness of this frequency transfer ability was proportional to the nonlinear ME coefficient a ME nonlin: Recently, for Metglas/Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 laminates, a ME nonlin was shown to have an optimum value near H dc ¼ 0.…”
mentioning
confidence: 99%
“…11 Recently, a modulation mode sensor which used a 2nd order ME nonlinearity was reported that transferred low-frequency target signals to higher frequencies. 12 In this method, an exciting carrier signal provided an effective means to reduce 1/f noise, to increase the signal-to-noise ratio (SNR), and to mitigate vibrational noise that is compared to a conventional passive mode scheme. 13 The effectiveness of this frequency transfer ability was proportional to the nonlinear ME coefficient a ME nonlin: Recently, for Metglas/Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 laminates, a ME nonlin was shown to have an optimum value near H dc ¼ 0.…”
mentioning
confidence: 99%
“…Significantly lower equivalent magnetic noise floors have been obtained in this study, consistent with prior predictions. 12 …”
Section: Experiments and Discussionmentioning
confidence: 99%
“…[14][15][16] The value of a ME nonlin at H dc ¼ 0 was determined to be 13 V=ðcm À Oe 2 ) for n ¼ 2, which represents an improvement of 6 times over previously reported values. 12 Figure 2(a) shows the linear ME voltage coefficient a ME for the same structures for different values of n. a ME was measured using a lock-in amplifier, as a function of H DC and in response to H AC ¼ 1 Oe at f ¼ 1 kHz that was driven by a Helmholtz coil. With increasing H DC , a ME increased quickly from zero at H DC ¼ 0 to a maximum value at a particular H DC (which is referred as H optim ) and then declined to zero for H DC !…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, to date, all investigations of the nonlinear ME coefficient, which is the physical basis of the frequency modulation method, have been reported using the same laminate structure as that used in the passive mode. 11 Due to a dependence of the different orders of nonlinearity on the magnetostrictive material, the structure resulting in a maximum nonlinear ME coefficient may not be the same as for the linear ME effect used in the passive mode. However, any investigations of the ME laminate structure that optimize the mode have not yet been performed.…”
mentioning
confidence: 99%